Anti-diabetic Effects of Cinnamon Extract in Alloxan-Induced Diabetic Rats in Comparison with Oral Hypoglycemic Drugs - Muhammad Sajid Khan, Ahmad Azmi, Syed Hyder Raza Naqvi, Tabinda Taqi , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2014)
Objectives: To observe the anti-diabetic efficacy of herbal plant in diabetes mellitus in comparison with conventional oral hypoglycemic drugs in animal model. Study Design: Experimental, Comparative. Place and duration: Department of Physiology, AL-Tibri Medical College & Hospital, ISRA University Karachi Campus, from July 2013 to December 2013. Material and Methods: Sixty albino rats divided into six groups each is further subdivided into two groups. Diabetes was induced by single dose of intraperitoneal injection of alloxan 150mg/kg body weight. Ethanol based cinnamon stern bark extract was prepared with working solution of acarbose and tolbutamide. After induction of diabetes when blood sugar lei el reaches to 250mg/dl the animal was used for further study. Blood sugar and serum insulin were measured to evaluate the antidiabetic effects of cinnamon bark extract. The data was collected and entered into data sheet of SPSS version 17. For analysis of data student T test and one way ANOVA was used. Results: A significant reduction of blood glucose level was noted in cinnamon extracts treated groups with marked improvement in the serum insulin level. Tolbutamide and acarbose treated groups showed better anti diabetic effect as compare to cinnamon extract treated groups (p value=0.007 and 0.012), but cinnamon extract treated group showed synergetic effect when it was given in combination with tolbutamide and acarbose having significant p value=0.001 and 0.011 respectively. Conclusion: Cinnamomum cassia extract has good synergetic effect when it is used with conventional anti diabetic therapy but alone its anti-diabetic efficacy is minimal in comparison with other oral hypoglycemic agents.